Kinerja Solvabilitas BCA Syariah: analisis debt to equity ratio tahun 2020–2024 - Arini, Titania Putri; Nur Aisyah, Esy (Maliki Interdisciplinary Journal, 2026)
This study aims to assess the solvency performance of Bank BCA Syariah during the 2020–2024 period using the Debt to Equity Ratio (DER) as the primary indicator. DER is applied to evaluate the bank’s ability to meet its long-term obligations based on its capital structure. The research uses secondary data obtained from the annual financial statements of Bank BCA Syariah. A descriptive quantitative approach is employed to identify trends, variations, and the stability of DER over the observed years. The findings indicate that the bank’s DER remains relatively stable and within acceptable levels according to Islamic banking standards, although fluctuations occur due to asset growth, liability composition changes, and capital management policies. Overall, the solvency condition of Bank BCA Syariah during the study period is considered healthy and capable of supporting its operational sustainability. These results provide valuable insights for management and regulators in evaluating the bank’s capital resilience amid ongoing economic challenges.